Transformasi Akuntansi Digital Dalam Menghadapi Tantangan Dan Peluang Era Digital - Hasanah, Uswatun (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2024)
Digital transformation has significantly altered accounting practices, enabling higher efficiency, accuracy, and transparency through the adoption of advanced technologies such as artificial intelligence (AI), blockchain, and cloud computing. This study aims to analyze the implementation of digital accounting at General Electric (GE) and PT Telkom Indonesia Tbk as case studies, highlighting the challenges and opportunities arising from the transformation process. The research method employs a descriptive qualitative approach by reviewing secondary data from various credible sources. The findings reveal that the implementation of technologies such as ERP systems, process automation, and data analytics has enhanced operational efficiency, data-driven decision-making, and financial reporting transparency. However, challenges such as cybersecurity, high costs, and the need for continuous training remain significant barriers. In conclusion, digital accounting transformation offers substantial strategic benefits but requires a holistic approach to address these challenges.